Low free 25-hydroxyvitamin D and high vitamin D binding protein and parathyroid hormone in obese Caucasians. A complex association with bone? - Elisa Saarnio; Minna Pekkinen; Suvi T Itkonen; Virpi Kemi; Heini Karp; Kaisa K Ivaska; Juha Risteli; Marja-Kaisa Koivula; Merja Kärkkäinen; Outi Mäkitie; Harri Sievänen; Christel Lamberg-Allardt (PLoS ONE, 2018)
Studies have shown altered vitamin D metabolism in obesity. We assessed differences between obese and normal-weight subjects in total, free, and bioavailable 25-hydroxyvitamin D (25(OH)D, 25(OH)DFree, and 25(OH)DBio, respectively), vitamin D binding protein (DBP), parathyroid hormone (PTH) and bone traits.595 37-47-year-old healthy Finnish men and women stratified by BMI were examined in this cross-sectional study. Background characteristic and intakes of vitamin D and calcium were collected. The concentrations of 25(OH)D, PTH, DBP, albumin and bone turnover markers were determined from blood. 25(OH)DFree and 25(OH)DBio were calculated. pQCT was performed at radius and tibia.Mean±SE (ANCOVA) 25(OH)DFree (10.8±0.6 vs 12.9±0.4 nmol/L; P = 0.008) and 25(OH)DBio (4.1±0.3 vs 5.1±0.1 nmol/L; P = 0.003) were lower in obese than in normal-weight women. In men, 25(OH)D (48.0±2.4 vs 56.4±2.0 nmol/L, P = 0.003), 25(OH)DFree (10.3±0.7 vs 12.5±0.6 pmol/L; P = 0.044) and 25(OH)DBio (4.2±0.3 vs 5.1±0.2 nmol/L; P = 0.032) were lower in obese. Similarly in all subjects, 25(OH)D, 25(OH)DFree and 25(OH)DBio were lower in obese (P<0.001). DBP (399±12 vs 356±7mg/L, P = 0.008) and PTH (62.2±3.0 vs 53.3±1.9 ng/L; P = 0.045) were higher in obese than in normal-weight women. In all subjects, PTH and DBP were higher in obese (P = 0.047and P = 0.004, respectively). In obese women, 25(OH)D was negatively associated with distal radius trabecular density (R2 = 0.089, P = 0.009) and tibial shaft cortical strength index (CSI) (R2 = 0.146, P = 0.004). 25(OH)DFree was negatively associated with distal radius CSI (R2 = 0.070, P = 0.049), radial shaft cortical density (CorD) (R2 = 0.050, P = 0.045), and tibial shaft CSI (R2 = 0.113, P = 0.012). 25(OH)DBio was negatively associated with distal radius CSI (R2 = 0.072, P = 0.045), radial shaft CorD (R2 = 0.059, P = 0.032), and tibial shaft CSI (R2 = 0.093, P = 0.024).The associations between BMI and 25(OH)D, 25(OH)DFree, and 25(OH)DBio, DBP, and PTH suggest that obese subjects may differ from normal-weight subjects in vitamin D metabolism. BMI associated positively with trabecular bone traits and CSI in our study, and slightly negatively with cortical bone traits. Surprisingly, there was a negative association of free and bioavailable 25(OH)D and some of the bone traits in obese women.